A tetratin triphosphide / hard carbon negative electrode composite material and its preparation method and application
By compounding Sanfu and Four Tin and Hard Carbon Materials, SN4P3/Hard Carbon negative composite materials are prepared, and the problem of poor comparison of the existing sodium ion battery negative electrode materials has poor capacity and cycle performance. And low -cost electrochemical performance.
Patent Information
- Application Number
- CN202411319529.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-09-23
AI Technical Summary
The existing sodium ion battery negative electrode materials have problems such as low specific capacity, poor circulation performance and high cost, and it is difficult to have high specific energy, long life and low cost.
The three -phosphorus four tin (SN4P3) compounds the hard carbon material, prepares a pre -compound charcoal black SN4P3 through the ball mill, and is fully mixed with the hard carbon to form SN4P3/hard carbon negative composite material.
It significantly improves the ratio of negative materials, improves circulation stability and electrochemical performance, and simplifies the preparation process and reduces production costs.
Smart Images

Figure CN118833786B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a tetratin triphosphide / hard carbon negative electrode composite material and a preparation method and application thereof. Background Art
[0002] In recent years, sodium-ion batteries have received extensive attention and development investment due to their advantages such as high natural abundance of sodium, low cost and high safety, and are expected to be used in technical fields such as power vehicles and large-scale energy storage. However, since the ionic radius of sodium ions (1.02 angstroms) is more than 30% higher than that of lithium ions (0.76 angstroms), it leads to a series of problems such as greater volume expansion rate, low coulombic efficiency and slow reaction kinetics.
[0003] At present, the manufacture of high-energy-density sodium-ion batteries is mainly restricted by the development of high-performance negative electrode materials. The negative electrode materials of sodium-ion batteries mainly include hard carbon negative electrode materials and alloy negative electrode materials based on alloying reactions. Hard carbon has the advantages of small volume expansion during the charge and discharge process and long cycle life. It is currently the most commercially significant negative electrode material for sodium-ion batteries, but its specific capacity is generally lower than 250 mAh / g, and it has disadvantages such as low first coulomb efficiency and low compaction density, which cannot meet the needs of high-energy sodium-ion batteries for negative electrodes. Alloy negative electrode materials often show high specific capacity when used as negative electrodes for sodium-ion batteries, but due to the huge volume expansion of such materials during the embedding and conversion process, they will agglomerate, crush and even eventually be electrochemically inactivated, which ultimately leads to poor cycle stability and safety. Therefore, the negative electrode materials for sodium-ion batteries in the prior art all have certain defects, and it is difficult to have excellent properties such as high specific capacity, excellent cycle performance, low electrochemical reaction potential, and good conductivity.
[0004] CN117691073A discloses a biomass-based hard carbon / alloy negative electrode composite material and its preparation method and application. The invention uses biomass materials or hard carbon products directly as carbon sources, disperses the carbon sources in water or organic solvents, adds metal sources for preparing alloy negative electrode materials, and stirs them thoroughly to achieve internal nucleation growth of the metal sources in the carbon source through hydrothermal or solvent thermal reactions, and finally obtains the biomass-based hard carbon / alloy negative electrode composite material through high-temperature calcination and carbonization. However, this technical solution introduces alloy negative electrode materials on the basis of carbon-based negative electrodes through hydrothermal or solvent thermal processes. Although the performance of negative electrode materials has been improved to a certain extent, the newly added process steps are relatively complicated, and energy consumption and production costs have increased, which is not conducive to industrial promotion.
[0005] CN117638058A discloses a tin phosphide-based negative electrode material and its preparation method and application. The invention first prepares metal phosphide by ball milling, and then mixes the metal phosphide with graphite or expanded graphite by ball milling in an inert atmosphere to prepare a phosphide-based mixed negative electrode material. However, the ball milling process in this technology will significantly change the pore structure of the hard carbon material. The hard carbon after ball milling has many defects and small crystallite size, has lower low potential platform capacity and lower first coulomb efficiency, and the electrochemical performance is significantly reduced.
[0006] Therefore, the development of high-performance sodium-ion battery negative electrode materials with the advantages of high capacity, long life and low cost is of great significance for the industrialization and large-scale application of sodium-ion batteries. Summary of the invention
[0007] In view of this, it is necessary to provide a tetratin phosphide / hard carbon negative electrode composite material and its preparation method and application to address the above problems. The present invention uses tin, phosphorus and carbon black as raw materials to synthesize modified tetratin phosphide (Sn4P3) of pre-compounded carbon black, and uses the hard carbon material with the most commercial development potential in sodium ion batteries as the main body to further compound to obtain a tetratin phosphide / hard carbon negative electrode composite material (Sn4P3 / hard carbon negative electrode composite material). The present invention, on the basis of not destroying the structure and electrochemical properties of the hard carbon material itself, composites the alloy material to achieve a significant improvement in the specific capacity of the negative electrode material, obtains a composite negative electrode material with better comprehensive performance, and solves the problems of low specific capacity of hard carbon negative electrode materials and poor cycle performance of phosphorus-based materials in the prior art.
[0008] To achieve the above object, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a method for preparing a tetratin triphosphide / hard carbon negative electrode composite material, comprising the following steps:
[0010] Step S1, mixing a tin source, a phosphorus source and carbon black to obtain a precursor, and ball-milling the precursor to obtain modified Sn4P3 of pre-composite carbon black;
[0011] Step S2, fully mixing the modified Sn4P3 of the pre-composite carbon black with hard carbon to obtain a Sn4P3 / hard carbon mixture;
[0012] Step S3, drying the Sn4P3 / hard carbon mixture to obtain.
[0013] Furthermore, in step S1, the tin source is one or more of tin powder, SnCl2, and SnCl4; the phosphorus source is one or more of red phosphorus and sodium phosphate; and the carbon black is one or more of SuperP, acetylene black, Ketjen black, carbon nanotubes, graphene, and conductive graphite.
[0014] Furthermore, in step S1, the molar ratio of tin to phosphorus in the tin source and the phosphorus source is (4-8):(3-6).
[0015] Furthermore, in step S1, the mass of the carbon black is 1% to 50% of the sum of the mass of the tin source and the phosphorus source.
[0016] Furthermore, in step S1, the ball milling method is to load the precursor and the ball milling medium into a ball milling jar, and then install it on a ball mill for ball milling.
[0017] Preferably, the ball milling can be performed once or multiple times; different raw materials can be added in batches during multiple ball milling to finally obtain the modified Sn4P3 of pre-composite carbon black. For example, the precursor in the first ball milling is a mixture of tin source and phosphorus source, and the second ball milling is a mixture of the product of the first ball milling and carbon black, and finally the modified Sn4P3 of pre-composite carbon black is obtained after multiple ball milling.
[0018] Preferably, the ball milling jar and the ball milling medium are made of zirconium dioxide, stainless steel, tungsten carbide, agate or corundum; the ball milling medium is a ball milling bead with a particle size of 0.1 to 50 mm, and the ball to material ratio is (1 to 50):1.
[0019] Furthermore, in step S1, the ball milling speed is 100-1000 rpm, and the ball milling time is 5-50 h.
[0020] Furthermore, in step S2, the mass ratio of the modified Sn4P3 and the hard carbon of the pre-compounded carbon black is 1:(1~100).
[0021] Furthermore, the mixing method of step S2 is wet mixing, and the wet mixing is to add the modified Sn4P3 of the pre-compounded carbon black and the hard carbon into a mixer and add a dispersant to mix them.
[0022] Furthermore, the mixing method of step S2 may be dry mixing, and the dry mixing does not add a dispersant.
[0023] Preferably, in step S2, the mixing speed is 200-2500 rpm, and the mixing time is 5-720 min.
[0024] Preferably, in step S2, the dispersant is one or more of water, ethanol, isopropanol, n-hexane, cyclohexane and toluene; the mass ratio of the total mass of the modified Sn4P3 and hard carbon of the pre-composite carbon black to the dispersant is 1:(5~50).
[0025] More preferably, the wet mixing includes ultrasonic wet mixing or wet gradient mixing; the ultrasonic wet mixing is to ultrasonically treat the raw materials before adding them into the mixer; the wet gradient mixing is to set the mixing process as a multi-stage mixing program.
[0026] Furthermore, in step S3, the drying temperature is 40-100° C., and the drying time is 5-36 hours.
[0027] In a second aspect, the present invention provides a Sn4P3 / hard carbon negative electrode composite material prepared by the above method.
[0028] In a third aspect, the present invention provides an application of the Sn4P3 / hard carbon negative electrode composite material or the method for preparing the Sn4P3 / hard carbon negative electrode composite material in sodium ion batteries.
[0029] Furthermore, the negative electrode material used in the sodium ion battery is a Sn4P3 / hard carbon negative electrode composite material.
[0030] The beneficial effects of the present invention are:
[0031] (1) The present invention selects Sn4P3 (tetratin triphosphide) with high capacity and high conductivity and the most promising hard carbon negative electrode as raw materials, and mixes them to prepare Sn4P3 / hard carbon composite electrodes; the present invention prepares Sn4P3 pre-compounded with carbon black by ball milling. Carbon black can disperse Sn4P3 particles, effectively alleviate volume expansion and segregation or agglomeration of Sn during the cycle, reduce internal stress of the material and improve the stability of the material. It can also effectively connect the dispersed Sn4P3 in series, so that the mixed material composed of it and hard carbon has higher ion diffusion capacity, increases the utilization rate of the material, and thus has higher capacity at high current density. In addition, the present invention can reduce the particle size of Sn4P3 by pre-compounding carbon black, which helps it to be better dispersed in the gaps of hard carbon, improve space utilization, increase volume energy density, alleviate local volume expansion problems, inhibit material pulverization and deactivation, and enhance electrochemical performance.
[0032] (2) The present invention avoids the destruction of the hard carbon material structure during the high-energy ball milling mixing process through the pretreatment and secondary mixing process of Sn4P3, exerts the sodium storage / removal capacity of the two components, and significantly improves the material specific capacity.
[0033] (3) The preparation process of the present invention is simple and easy to prepare on a large scale. The Sn4P3 / hard carbon composite negative electrode material prepared by the present invention is applied to sodium ion batteries, so that the batteries have higher specific capacity, excellent rate performance and cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 is the XRD pattern of the Sn4P3 / hard carbon negative electrode composite material in Example 1 of the present invention;
[0035] Figure 2 is a SEM image of the Sn4P3 / hard carbon negative electrode composite material in Example 1 of the present invention;
[0036] Figure 3is the charge and discharge curve of the negative electrode materials provided in Examples 1, 4, 5, 6, 7 and Comparative Example 3 of the present invention when in use;
[0037] Figure 4 It is a comparison chart of the rate performance of the negative electrode materials provided in Examples 1, 4, 5, 6, 7 and Comparative Example 3 of the present invention when in use. DETAILED DESCRIPTION
[0038] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be further clearly and completely described in combination with the embodiments of the present invention. It should be noted that the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0039] In the description of the present invention, it should be noted that, if the specific conditions are not specified in the examples, the experiments were carried out according to conventional conditions or the conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not specified, are all conventional products that can be purchased commercially. Example 1
[0040] A method for preparing a tetratin triphosphide / hard carbon negative electrode composite material comprises the following steps:
[0041] Step S1, weighing 3.561g of tin powder, 0.620g of red phosphorus and 0.836g of conductive carbon black (Super P), briefly grinding and mixing to obtain a precursor, transferring the precursor to a tungsten carbide ball milling jar under an argon atmosphere, adding tungsten carbide ball milling beads according to a ball-to-material ratio of 10:1, sealing the ball milling jar and placing it on a ball mill for ball milling, the ball milling speed is 400rpm, and the ball milling is continued for 33h. After the ball milling is completed, the ball milling beads are sieved out, and the product is transferred to a mortar and ground to obtain a modified Sn4P3 (tetratin triphosphide) pre-compounded with 20% carbon black;
[0042] Step S2, weigh 0.720 g of the modified Sn4P3 pre-compounded with 20% carbon black obtained in step S1 and 1.400 g of hard carbon, put them in a mixer, add 21.2 g of ethanol as a dispersant, mix them thoroughly at 500 rpm for 15 min, and obtain a Sn4P3 / hard carbon mixture;
[0043] Step S3, taking out the Sn4P3 / hard carbon mixture, placing it in a drying oven, and drying it at 60° C. for 12 h.
[0044] The Sn4P3 content in the Sn4P3 / hard carbon negative electrode composite material prepared by the preparation method of this embodiment is 30%. The prepared Sn4P3 / hard carbon negative electrode composite material was subjected to XRD test and SEM scanning electron microscope scanning, and the results are as follows: Figure 1 and Figure 2 As shown. Figure 1 The characteristic peaks of the Sn4P3 component can be observed, and the sharp cone peaks show good crystallinity, while the characteristic peaks of hard carbon with a high degree of amorphization are relatively inconspicuous. Figure 2 It can be seen that hard carbon has a block structure with a particle size ranging from a few microns to more than ten microns. The Sn4P3 modified by pre-composite carbon black is a loose agglomerate particle, which is smaller than the block particles of hard carbon. The composite material after the two are blended is composed of Sn4P3 as an additive discretely distributed in the gaps between large hard carbon particles, or attached to the surface of hard carbon, filling the gaps in the original structure. Example 2
[0045] A method for preparing a tetratin triphosphide / hard carbon negative electrode composite material comprises the following steps:
[0046] Step S1, weighing 3.561g of tin powder, 0.620g of red phosphorus and 0.418g of conductive carbon black, and mixing them by simple grinding to obtain a precursor, transferring the precursor to a tungsten carbide ball mill under an argon atmosphere, adding tungsten carbide ball milling beads according to a ball-to-material ratio of 10:1, sealing the ball milling jar and placing it on a ball mill for ball milling, the ball milling speed is 400rpm, and the ball milling is continued for 33h. After the ball milling is completed, the ball milling beads are sieved out, and the product is transferred to a mortar and ground to obtain a modified Sn4P3 pre-compounded with 10% carbon black;
[0047] Step S2, weigh 0.660 g of the modified Sn4P3 pre-compounded with 10% carbon black obtained in step S1 and 1.400 g of hard carbon, put them in a mixer, add 20.6 g of ethanol as a dispersant, mix them thoroughly at 500 rpm for 15 min, and obtain a Sn4P3 / hard carbon mixture;
[0048] Step S3, taking out the Sn4P3 / hard carbon mixture, placing it in a drying oven, and drying it at 60° C. for 12 h.
[0049] The Sn4P3 content in the Sn4P3 / hard carbon negative electrode composite material prepared by the preparation method of this embodiment is 30%. Example 3
[0050] A method for preparing a tetratin triphosphide / hard carbon negative electrode composite material comprises the following steps:
[0051] Step S1, weighing 3.561g of tin powder and 0.620g of red phosphorus and grinding them for 5min, then adding 0.209g of conductive carbon black, briefly grinding and mixing to obtain a precursor, transferring the precursor to a tungsten carbide ball milling jar under an argon atmosphere, adding tungsten carbide ball milling beads according to a ball-to-material ratio of 10:1, sealing the ball milling jar and placing it on a ball mill for ball milling, the ball milling speed is 400rpm, and the ball milling is continued for 33h. After the ball milling is completed, the ball milling beads are sieved out, and the product is transferred to a mortar and ground to obtain a modified Sn4P3 pre-compounded with 5% carbon black;
[0052] Step S2, weigh 0.630 g of the modified Sn4P3 pre-compounded with 20% carbon black obtained in step S1 and 1.400 g of hard carbon, put them in a mixer, add 20.3 g of ethanol as a dispersant, mix them thoroughly at 500 rpm for 15 min, and obtain a Sn4P3 / hard carbon mixture;
[0053] Step S3, taking out the Sn4P3 / hard carbon mixture, placing it in a drying oven, and drying it at 60° C. for 12 h.
[0054] The Sn4P3 content in the Sn4P3 / hard carbon negative electrode composite material prepared by the preparation method of this embodiment is 30%. Example 4
[0055] A method for preparing a tetratin triphosphide / hard carbon negative electrode composite material comprises the following steps:
[0056] Step S1, weighing 3.561g of tin powder, 0.620g of red phosphorus and 0.836g of conductive carbon black, and mixing them by simple grinding to obtain a precursor, transferring the precursor to a tungsten carbide ball mill under an argon atmosphere, adding tungsten carbide ball milling beads according to a ball-to-material ratio of 10:1, sealing the ball milling jar and placing it on a ball mill for ball milling, the ball milling speed is 400rpm, and the ball milling is continued for 33h. After the ball milling is completed, the ball milling beads are sieved out, and the product is transferred to a mortar and ground to obtain a modified Sn4P3 pre-compounded with 20% carbon black;
[0057] Step S2, weigh 0.120 g of the modified Sn4P3 pre-compounded with 20% carbon black obtained in step S1 and 1.900 g of hard carbon, put them in a mixer, add 20.2 g of ethanol as a dispersant, mix them thoroughly at 500 rpm for 15 min, and obtain a Sn4P3 / hard carbon mixture;
[0058] Step S3, taking out the Sn4P3 / hard carbon mixture, placing it in a drying oven, and drying it at 60° C. for 12 h.
[0059] The Sn4P3 content in the Sn4P3 / hard carbon negative electrode composite material prepared by the preparation method of this embodiment is 5%. Example 5
[0060] A method for preparing a tetratin triphosphide / hard carbon negative electrode composite material comprises the following steps:
[0061] Step S1, weighing 3.561g of tin powder, 0.620g of red phosphorus and 0.836g of conductive carbon black, and mixing them by simple grinding to obtain a precursor, transferring the precursor to a tungsten carbide ball mill under an argon atmosphere, adding tungsten carbide ball milling beads according to a ball-to-material ratio of 10:1, sealing the ball milling jar and placing it on a ball mill for ball milling, the ball milling speed is 400rpm, and the ball milling is continued for 33h. After the ball milling is completed, the ball milling beads are sieved out, and the product is transferred to a mortar and ground to obtain a modified Sn4P3 pre-compounded with 20% carbon black;
[0062] Step S2, weigh 0.288 g of the modified Sn4P3 pre-compounded with 20% carbon black obtained in step S1 and 1.760 g of hard carbon, put them in a mixer, add 20.5 g of ethanol as a dispersant, mix them thoroughly at 500 rpm for 15 min, and obtain a Sn4P3 / hard carbon mixture;
[0063] Step S3, taking out the Sn4P3 / hard carbon mixture, placing it in a drying oven, and drying it at 60° C. for 12 h.
[0064] The Sn4P3 content in the Sn4P3 / hard carbon negative electrode composite material prepared by the preparation method of this embodiment is 12%. Example 6
[0065] A method for preparing a tetratin triphosphide / hard carbon negative electrode composite material comprises the following steps:
[0066] Step S1, weighing 3.561g of tin powder, 0.620g of red phosphorus and 0.836g of conductive carbon black, and mixing them by simple grinding to obtain a precursor, transferring the precursor to a tungsten carbide ball mill under an argon atmosphere, adding tungsten carbide ball milling beads according to a ball-to-material ratio of 10:1, sealing the ball milling jar and placing it on a ball mill for ball milling, the ball milling speed is 400rpm, and the ball milling is continued for 33h. After the ball milling is completed, the ball milling beads are sieved out, and the product is transferred to a mortar and ground to obtain a modified Sn4P3 pre-compounded with 20% carbon black;
[0067] Step S2, weigh 0.480 g of the modified Sn4P3 pre-compounded with 20% carbon black obtained in step S1 and 1.600 g of hard carbon, put them in a mixer, add 20.8 g of ethanol as a dispersant, mix them thoroughly at 500 rpm for 15 min, and obtain a Sn4P3 / hard carbon mixture;
[0068] Step S3, taking out the Sn4P3 / hard carbon mixture, placing it in a drying oven, and drying it at 60° C. for 12 h.
[0069] The Sn4P3 content in the Sn4P3 / hard carbon negative electrode composite material prepared by the preparation method of this embodiment is 20%. Example 7
[0070] A method for preparing a tetratin triphosphide / hard carbon negative electrode composite material comprises the following steps:
[0071] Step S1, weighing 3.561g of tin powder, 0.620g of red phosphorus and 0.836g of conductive carbon black, and mixing them by simple grinding to obtain a precursor, transferring the precursor to a tungsten carbide ball mill under an argon atmosphere, adding tungsten carbide ball milling beads according to a ball-to-material ratio of 10:1, sealing the ball milling jar and placing it on a ball mill for ball milling, the ball milling speed is 400rpm, and the ball milling is continued for 33h. After the ball milling is completed, the ball milling beads are sieved out, and the product is transferred to a mortar and ground to obtain a modified Sn4P3 pre-compounded with 20% carbon black;
[0072] Step S2, weigh 0.960 g of the modified Sn4P3 pre-compounded with 20% carbon black obtained in step S1 and 1.200 g of hard carbon, put them in a mixer, add 21.6 g of ethanol as a dispersant, mix them thoroughly at 500 rpm for 15 min, and obtain a Sn4P3 / hard carbon mixture;
[0073] Step S3, taking out the Sn4P3 / hard carbon mixture, placing it in a drying oven, and drying it at 60° C. for 12 h.
[0074] The Sn4P3 content in the Sn4P3 / hard carbon negative electrode composite material prepared by the preparation method of this embodiment is 40%. Example 8
[0075] A method for preparing a tetratin triphosphide / hard carbon negative electrode composite material comprises the following steps:
[0076] Step S1, weighing 3.561g of tin powder, 0.620g of red phosphorus and 0.836g of conductive carbon black, and mixing them by simple grinding to obtain a precursor, transferring the precursor to a tungsten carbide ball mill under an argon atmosphere, adding tungsten carbide ball milling beads according to a ball-to-material ratio of 10:1, sealing the ball milling jar and placing it on a ball mill for ball milling, the ball milling speed is 400 rpm, and the ball milling is continued for 33h. After the ball milling is completed, the ball milling beads are sieved out, and the product is transferred to a mortar and ground to obtain a modified Sn4P3 pre-compounded with 20% carbon black;
[0077] Step S2, weigh 1.400g of hard carbon powder, pour into 50mL of anhydrous ethanol solution, stir for 5min, place in an ultrasonic cleaner and continue ultrasonication for 15min until the powder is well dispersed in the anhydrous ethanol solution; then weigh 0.720g of the modified Sn4P3 pre-compounded with 20% carbon black obtained in step S1, add it to the anhydrous ethanol dispersed with hard carbon powder under stirring, and continue ultrasonication for 60min. During the ultrasonication process, the water needs to be changed regularly to keep the water temperature constant at room temperature; after the ultrasonication is completed, pour it into a mixer and mix it thoroughly at 500rpm for 15min to obtain a Sn4P3 / hard carbon mixture;
[0078] Step S3, taking out the Sn4P3 / hard carbon mixture, placing it in a drying oven, and drying it at 60° C. for 12 h.
[0079] The Sn4P3 content in the Sn4P3 / hard carbon negative electrode composite material prepared by the preparation method of this embodiment is 30%. Example 9
[0080] A method for preparing a tetratin triphosphide / hard carbon negative electrode composite material comprises the following steps:
[0081] Step S1, weighing 3.561g of tin powder, 0.620g of red phosphorus and 0.836g of conductive carbon black, and mixing them by simple grinding to obtain a precursor, transferring the precursor to a tungsten carbide ball mill under an argon atmosphere, adding tungsten carbide ball milling beads according to a ball-to-material ratio of 10:1, sealing the ball milling jar and placing it on a ball mill for ball milling, the ball milling speed is 400rpm, and the ball milling is continued for 33h. After the ball milling is completed, the ball milling beads are sieved out, and the product is transferred to a mortar and ground to obtain a modified Sn4P3 pre-compounded with 20% carbon black;
[0082] Step S2: Weigh 1.400 g of hard carbon powder and 0.720 g of modified Sn4P3 pre-compounded with 20% carbon black obtained in step S1 and place them in a special container of a centrifugal mixer, add 21.2 g of anhydrous ethanol and balance the mass. Set the mixer to a gradient mixing program, with a speed of 500 rpm for 60 s, 1000 rpm for 120 s, 2500 rpm for 180 s, and finally 500 rpm for 120 s to obtain a Sn4P3 / hard carbon mixture;
[0083] Step S3, taking out the Sn4P3 / hard carbon mixture, placing it in a drying oven, and drying it at 60° C. for 12 h.
[0084] The Sn4P3 content in the Sn4P3 / hard carbon negative electrode composite material prepared by the preparation method of this embodiment is 30%. Example 10
[0085] A method for preparing a tetratin triphosphide / hard carbon negative electrode composite material comprises the following steps:
[0086] Step S1, weighing 3.561g of tin powder, 0.620g of red phosphorus and 0.836g of conductive carbon black, and mixing them by simple grinding to obtain a precursor, transferring the precursor to a tungsten carbide ball mill under an argon atmosphere, adding tungsten carbide ball milling beads according to a ball-to-material ratio of 10:1, sealing the ball milling jar and placing it on a ball mill for ball milling, the ball milling speed is 400rpm, and the ball milling is continued for 33h. After the ball milling is completed, the ball milling beads are sieved out, and the product is transferred to a mortar and ground to obtain a modified Sn4P3 pre-compounded with 20% carbon black;
[0087] Step S2, weigh 1.400g of hard carbon powder and 0.720g of modified Sn4P3 pre-compounded with 20% carbon black obtained in step S1, and place them in a special container of a centrifugal mixer, and set the mixer to a gradient mixing treatment program, with a speed of 500rpm for 60s, 1000rpm for 120s, 2500rpm for 180s, and finally 500rpm for 120s to obtain a Sn4P3 / hard carbon mixture;
[0088] Step S3, taking out the Sn4P3 / hard carbon mixture, placing it in a drying oven, and drying it at 60° C. for 12 h.
[0089] The Sn4P3 content in the Sn4P3 / hard carbon negative electrode composite material prepared by the preparation method of this embodiment is 30%.
[0090] Comparative Example 1
[0091] A method for preparing a tetratin triphosphide / hard carbon negative electrode composite material comprises the following steps:
[0092] Step S1, weigh 3.561g of tin powder and 0.620g of red phosphorus, grind and mix briefly, and then transfer to a tungsten carbide ball mill under an argon atmosphere, add tungsten carbide ball milling beads according to a ball-to-material ratio of 10:1, seal the ball milling jar and place it on a ball mill for ball milling at a ball milling speed of 400rpm, and continue ball milling for 33h. After the ball milling is completed, the ball milling beads are sieved out, and the product is transferred to a mortar and ground to obtain an off-white powder Sn4P3;
[0093] Step S2, weighing 0.60 g of Sn4P3 obtained in step S1 and 1.400 g of hard carbon, placing them in a mixer, adding 20 g of ethanol as a dispersant, and mixing them thoroughly at a speed of 500 rpm for 15 min to obtain a Sn4P3 / hard carbon mixture;
[0094] Step S3, taking out the Sn4P3 / hard carbon mixture, placing it in a drying oven, and drying it at 60° C. for 12 h.
[0095] The Sn4P3 content in the Sn4P3 / hard carbon negative electrode composite material prepared by the preparation method of this embodiment is 30%.
[0096] Comparative Example 2
[0097] A method for preparing a tetratin triphosphide negative electrode material comprises the following steps:
[0098] Weigh 3.561 g of tin powder and 0.620 g of red phosphorus, grind and mix for 5 minutes, transfer to a tungsten carbide ball mill under an argon atmosphere, add tungsten carbide ball milling beads at a ball-to-material ratio of 10:1, seal the ball mill, set the speed to 400 rpm on the ball mill, and continue ball milling for 33 hours; after the ball milling is completed, after screening out the ball milling beads, transfer the product to a mortar and grind it to obtain Sn4P3, and use Sn4P3 directly as the negative electrode material.
[0099] Comparative Example 3
[0100] Hard carbon is directly used as the negative electrode material, that is, the Sn4P3 content is 0%.
[0101] Experimental testing
[0102] The negative electrode materials prepared in the above-mentioned embodiments and comparative examples were used as negative electrode active materials to prepare sodium ion battery negative electrodes, and button batteries were made to complete electrochemical performance tests.
[0103] The battery preparation method is as follows:
[0104] (1) Prepare a binder: dissolve 1.00 g of sodium carboxymethyl cellulose in 49.00 g of deionized water, stir and mix thoroughly to prepare a 2% mass fraction CMC binder for later use;
[0105] (2) The negative electrode materials (negative electrode active materials), conductive carbon black and binder (calculated by CMC mass) prepared in different embodiments and comparative examples were taken at a mass ratio of 8:1:1, added to sample bottles with different labels, and then added with a magnetic stirrer. After simple stirring, ultrasonic treatment was performed for 10 minutes, and then continued to stir for 6 hours until the components were completely mixed into a viscous slurry state;
[0106] (3) Take a copper foil of appropriate size, flatten it on a glass plate, and wipe the surface with ethanol; after waiting for the ethanol to evaporate, transfer the treated slurry to the surface of the copper foil, and use a manual coater to evenly apply the slurry to a thickness of 200 μm. After drying at room temperature for 30 minutes, transfer it to a vacuum oven at 60 °C and dry it in vacuum for 8 hours to obtain the electrode;
[0107] (4) Cut the prepared electrode into discs with a diameter of 14 mm, and cut the diaphragm into discs with a diameter of 18 mm; install each component in the order of positive electrode stainless steel shell - gasket - electrode to be tested - dripping electrolyte - diaphragm - dripping electrolyte - sodium metal sheet - gasket - spring sheet - negative electrode stainless steel shell, where pure metallic sodium is always used as the counter electrode on the negative electrode side, and the electrode to be tested is always on the positive electrode side; after assembly, use a button battery sealing machine for pressure packaging; before testing, the packaged battery needs to be left to stand for more than 12 hours.
[0108] In the half-cell system, the charge and discharge cut-off voltage range was selected from 0.01V to 1.50V, and the charge and discharge performance tests were carried out at multiple current densities (1C = 1000 mA / g). The test results are shown in Table 1. Figure 3 as well as Figure 4 As shown. Figure 3 The first charge and discharge curves of the sodium ion battery using the negative electrode materials prepared in Examples 1, 4, 5, 6, 7 and Comparative Example 3 are as follows: Figure 4 This is a comparison chart of the rate performance of sodium ion batteries using the negative electrode materials prepared in Examples 1, 4, 5, 6, 7 and Comparative Example 3.
[0109] Table 1
[0110] First coulombic efficiency% 0.1C first charge specific capacity mAh / g Compared with HC negative electrode, the specific capacity is improved by mAh / g Capacity retention rate after 100 0.5C charge and discharge cycles% Average coulombic efficiency after 100 charge and discharge cycles% Example 1 87.8 412.3 197.4 79.2 99.6 Example 2 87.4 443.3 228.4 78.3 99.4 Example 3 87.4 429.4 214.5 74.6 99.5 Example 4 79.1 273.5 58.6 81.3 99.3 Example 5 78.7 310.6 95.7 80.2 99.7 Example 6 82.4 372.9 158.0 79.7 99.6 Example 7 83.8 473.5 258.6 75.9 99.7 Example 8 87.2 431.5 216.6 80.9 99.8 Example 9 87.4 448.9 234.0 81.6 99.6 Example 10 87.6 457.7 242.8 78.9 99.6 Comparative Example 1 88.0 470.3 255.4 59.8 98.3 Comparative Example 2 89.4 901.7 686.8 17.9 97.7 Comparative Example 3 83.1 214.9 - 96.2 99.1
[0111] As can be seen from Table 1, the sodium ion batteries using the Sn4P3 / hard carbon negative electrode composite materials prepared by the preparation methods provided in Examples 1 to 10 of the present invention as negative electrode active materials all have excellent electrochemical properties. When the content of Sn4P3 in the composite materials is the same, the Sn4P3 / hard carbon negative electrode composite materials prepared in Examples 1 to 3 and 8 to 10 have better cycle performance than the Sn4P3 / hard carbon negative electrode composite materials not modified with carbon black in Comparative Example 1, which confirms the effect of pre-composite carbon black modification on the improvement of material structure stability and electrochemical performance.
[0112] Compared with the common Sn4P3 negative electrode (Comparative Example 2), the Sn4P3 / hard carbon negative electrode composite material of the embodiment of the present invention significantly improves the cycle stability and has a higher capacity retention rate.
[0113] Compared with the common hard carbon negative electrode (Comparative Example 3), the Sn4P3 / hard carbon negative electrode composite materials prepared in Examples 1 to 10 of the present invention have significantly improved specific capacity and first coulombic efficiency.
[0114] Figure 3The first charge and discharge curve comparison diagram of the negative electrode materials prepared in Examples 1, 4, 5, 6, 7 and Comparative Example 3 shows that, based on the specific capacity of the hard carbon material, as the proportion of the pre-composite carbon black-modified Sn4P3 increases, the specific capacity of the Sn4P3 / hard carbon composite negative electrode material increases accordingly. This indicates that the preparation method of the present invention and the Sn4P3 / hard carbon composite material prepared therefrom have more excellent electrochemical properties.
[0115] Figure 4 This is a comparison chart of the rate performance of the negative electrode materials prepared in Examples 1, 4, 5, 6, 7 and Comparative Example 3, covering a current density range from 100 mA / g to 2000 mA / g. It can be seen that the composite negative electrode materials prepared in each embodiment at different current densities have higher specific capacity and excellent rate performance than the ordinary hard carbon negative electrode (Comparative Example 3).
[0116] Therefore, the tetratin triphosphide / hard carbon negative electrode composite material prepared by the present invention takes advantage of its strengths and avoids its weaknesses, and has the best comprehensive performance.
[0117] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a tetratin triphosphide / hard carbon negative electrode composite material, characterized in that: The steps include: Step S1, mixing a tin source, a phosphorus source and carbon black to obtain a precursor, and ball-milling the precursor to obtain modified Sn4P3 of pre-composite carbon black; Step S2, fully mixing the modified Sn4P3 of the pre-composite carbon black with hard carbon to obtain a Sn4P3 / hard carbon mixture; Step S3, drying the Sn4P3 / hard carbon mixture to obtain.
2. The method for preparing the tetratin phosphide / hard carbon negative electrode composite material according to claim 1, characterized in that: In step S1, the tin source is one or more of tin powder, SnCl2, and SnCl4; the phosphorus source is one or more of red phosphorus and sodium phosphate; and the carbon black is one or more of SuperP, acetylene black, Ketjen black, carbon nanotubes, graphene, and conductive graphite.
3. The method for preparing the tetratin phosphide / hard carbon negative electrode composite material according to claim 1, characterized in that: In step S1, the molar ratio of tin to phosphorus in the tin source and the phosphorus source is (4-8): (3-6); the mass of the carbon black is 1%-50% of the sum of the mass of the tin source and the phosphorus source.
4. The method for preparing the tetratin phosphide / hard carbon negative electrode composite material according to claim 1, characterized in that: The ball milling method is to load the precursor and the ball milling medium into a ball milling jar, and then install it on a ball mill for ball milling; the ball milling jar and the ball milling medium are made of zirconium dioxide, stainless steel, tungsten carbide, agate or corundum; the ball milling medium is a ball with a particle size of 0.1~50mm, and the ball-to-material ratio is (1~50):
1.
5. The method for preparing the tetratin phosphide / hard carbon negative electrode composite material according to claim 1, characterized in that: The ball milling speed is 100~1000rpm, and the ball milling time is 5~50h.
6. The method for preparing the tetratin phosphide / hard carbon negative electrode composite material according to claim 1, characterized in that: The mass ratio of the modified Sn4P3 and the hard carbon of the pre-compounded carbon black in step S2 is 1:(1~100).
7. The method for preparing the tetratin phosphide / hard carbon negative electrode composite material according to claim 1, characterized in that: The mixing method of step S2 is to add the modified Sn4P3 of the pre-compounded carbon black and the hard carbon into a mixer and add a dispersant for mixing; the mixing speed is 200~2500rpm, and the mixing time is 5~720min.
8. The method for preparing the tetratin triphosphide / hard carbon negative electrode composite material according to claim 7, characterized in that: In step S2, the dispersant is one or more of water, ethanol, isopropanol, n-hexane, cyclohexane and toluene; the mass ratio of the total mass of the modified Sn4P3 and hard carbon of the pre-composite carbon black to the dispersant is 1:(5~50).
9. The method for preparing the tetratin phosphide / hard carbon negative electrode composite material according to claim 1, characterized in that: In step S3, the drying temperature is 40-100°C, and the drying time is 5-36 hours.
10. A tetratin triphosphide / hard carbon negative electrode composite material, characterized in that: The method is prepared by any one of claims 1 to 9.
11. Use of the tetratin triphosphide / hard carbon negative electrode composite material according to claim 10 in a sodium ion battery.
Citation Information
Patent Citations
Biomass-based hard carbon / alloy anode composite material as well as preparation method and application thereof
CN117691073A
Battery composite electrode material and application thereof
CN113659126A
Porous carbon loaded tin phosphide composite material and preparation method thereof
CN117886282A